2009
DOI: 10.25011/cim.v32i6.10669
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antihyperglycemic effects of creatine and metformin in type II diabetic patients

Abstract: Clin Invest Med 2009; 32 (6): E322-E326. AbstractPurpose: To compare the antihyperglycemic effects of metformin and creatine in recently detected type II diabetics in a short-term clinical study. Methods: In a 14 day simmetrically randomized crossover study, recently detected type II diabetics received either creatine (2x3 g/day) or metformin (2x500 mg/day) for five days, followed by two days of washout, followed by crossover to the opposite treatment for the next five days. Fasting and post-prandial (-15, 60,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…We have previously reported that creatine stimulated insulin secretion in cultured pancreatic b-cells [9]. The present findings appear to confirm these results; however, it is rather speculative to account for the significant increase of insulin secretion while the hyperinsulinemia is a hallmark of type II diabetes.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We have previously reported that creatine stimulated insulin secretion in cultured pancreatic b-cells [9]. The present findings appear to confirm these results; however, it is rather speculative to account for the significant increase of insulin secretion while the hyperinsulinemia is a hallmark of type II diabetes.…”
Section: Discussionsupporting
confidence: 80%
“…It was recently reported that creatine is as effective as metformin (1,1-dimethylbiguanide), at the dose applied, regarding its ability to lower glucose in patients with newly detected type 2 diabetes mellitus [9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out in newly-diagnosed patients with the type 2 diabetes demonstrated that shortterm oral ingestion of creatine elicited a reduction of plasma glucose which was equal to the effects obtained by two common oral antihyperglycaemic agents: sulfonylurea [84] and metformin [85]. As evidenced in the recent meta-analysis [86], longer-term supplementation of creatine yielded indeterminate results regarding glycemic control, but creatine supplementation could be regarded as an adjuvant nutritional therapy with hypoglycemic effects, particularly when used in combination with exercise.…”
Section: Discussionmentioning
confidence: 92%
“…In a significant different model, however, creatine supplementation (20 g•d −1 for 2 weeks) was shown to prevent the drop in GLUT-4 protein expression induced by leg immobilization in healthy young men (+9% in the creatine group vs. −20% in the placebo group) [9]. In an open-label, cross-over study (with a 2-day washout period) involving a small sample of T2DM patients, creatine supplementation (6 g•d −1 for 5 days) was as effective as metformin (2 × 500 mg•d −1 ), a widely used anti-diabetic drug, in lowering blood glucose concentrations [52]. The human studies assessing the effect of creatine supplementation alone on glycemic control are summarized in Table 2.…”
Section: Effects Of Creatine Supplementation Alone On Glycemic Controlmentioning
confidence: 99%